Ethics through Literature : Ascetic and Aesthetic Reading in Western Culture - Stock, Brian (Book collections on Project MUSE., 2007)
"Why do we read? Based on a series of lectures delivered at the Historical Society of Israel in 2005, Brian Stock presents a model for relating ascetic and aesthetic principles in Western reading practices. Tracing the ascetic component of reading from Late Antiquity through the Renaissance and beyond, to Coleridge and Schopenhauer, Stock reveals the ascetic or ethical as a constant with the aesthetic serving as opposition, parallel force, and handmaiden, underscoring the historical consistency of the reading experience through the ages and across various media."--Jacket.